If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y-5+y+16=6y+20-3y
We simplify the equation to the form, which is simple to understand
5y-5+y+16=6y+20-3y
We move all terms containing y to the left and all other terms to the right.
+5y+1y-6y+3y=+20+5-16
We simplify left and right side of the equation.
+3y=+9
We divide both sides of the equation by 3 to get y.
y=3
| 3/4-d=2 | | 2z-31=-9y+24 | | -7a+4a=0 | | 2/9+y=-7/18 | | -4a-3a=-14 | | 5/7+1/4=7/28 | | m/5-7/3 | | -6n-5n=11 | | (-5t+4)-(2t-2)= | | -(93c-48d-24)= | | 5/7+1/4=7/27 | | 7+2x-5x=-2 | | 49r+28s+21= | | 5x+10+3x=60 | | 7-3p+7=-4 | | 2.5(-2.9r+1.6n-3.5)= | | x^2=-3/4 | | .25x+.40(p-x)=.30p | | y-10=5 | | 3r-46-25r=-51+r | | (9x-5)2=81 | | 2x=78 | | m-18=8x | | 34.6+4x/5=8.44 | | -5n-5n=-20 | | x^2+21x-2=0 | | (-8m^5n^7)/(4m^-2n^-2) | | y=2x^3+9x^2-24x+56 | | 7=x-6 | | x/6=20/32 | | 3(x+2.67)=2x | | 17x+13=17x-13 |